Implementing congestion avoidance mechanism in cluster based routing protocol for wireless mesh client networks - Adekiigbe, Adebanjo (Springer, 2015)
The wireless mesh network is a promising technology to help shape the world of pervasive communication for more comfortable, efficient and cheap wireless network platform. One of the challenges before this technology is congestion that causes packet loss. However, the challenge can be efficiently reduced if congestion avoidance mechanism is improvised into the routing protocols. In this paper, we proposed an improved congestion avoidance cluster based routing protocol (i-CBRPCA) for wireless clients in the mesh networks. In the mechanism, the traffic rate of source clusterhead is compared with the traffic rate of the receiving intermediate clusterhead and Arbitration Interframe Space Number of the sending clusterhead is increased or decreased depending on whether the traffic rate is decreased or increased. This congestion metric helps control the rate in order to have maximum allowable traffic traversing the intermediate clusterheads. Based on the simulation results, the proposed approach delivers high packets, reduced delay, delivers high throughput and lower packet loss when compared with CBRP.